Correlation between Age, Type of Fracture and Location of Long Bone Fracture on Length of Hospitalization of Post Op Patients - Samsir; Sulasri; Andi Arnoli (PT FORMOSA CENDEKIA GLOBAL, 2023)
Fracture is a problem with a fairly high incidence, one of the treatments is operative action. This study aims to determine the relationship between age, type of fracture, and location of long bone fractures on the length of postoperative hospitalization at Makassar City Government Hospital. This research is a type of observational analytic research using a cross sectional technique. The sampling technique used was purposive sampling with a total of 50 respondents recorded in the medical records of the Makassar City Government Hospital. The results of this study found that respondents in the category of elderly and non-elderly had no relationship to the length of stay in the Post-Operative (p = 0.361). As for the type of fracture experienced by the respondent, it had a relationship to the length of postoperative hospitalization (p = 0.004). The location of the fracture experienced by the respondent also had a relationship to the length of postoperative hospitalization (p = 0.030).